Synthesis of graphene quantum dots-coated hierarchical CuO microspheres composite for use as binder-free anode for lithium-ion batteries - Kim, Jongmin; Jang, Wooree; Kim, Ji Hoon; Yang, Cheol-Min (ELSEVIER SCI LTD, 2021)
There is an urgent need to develop improved anode materials for lithium-ion batteries (LIBs). Herein, we report the synthesis of a graphene quantum dots (GQDs)-coated hierarchical nanoflake-based CuO microspheres (H-CuO) composite on Cu foam via a one-pot hydrothermal technique for use as a binder-free anode for LIBs. The carboxyl-functionalized GQD coating on H-CuO not only results in lower charge-transfer resistance and enhanced electrical conductivity but also prevents the dissolution and agglomeration of the electrode. The GODs/H-CuO composite anode exhibits a reversible capacity as high as 609 mAh g(-1) (pristine H-CuO: 61 mAh g(-1)) after 200 cycles at 0.2 A g(-1). It also shows long-term cycling stability, exhibiting a capacity retention rate of 79.4% after 1000 cycles (pristine H-CuO: 0.7%) at a high current density (2 A g(-1)) and improved initial coulombic efficiency at 88.2% (pristine H-CuO: 75.2%). The superior electrochemical properties of the GQDs/H-CuO composite anode are attributable to the graphene networks, which help maintain a high specific surface area and effectively protect the anodic active material from forming an unstable solid electrolyte interface layer. The proposed strategy for fabricating the GQD-coated metal oxide microsphere-based anode should contribute to the development of next-generation LIBs with improved electrochemical performance.
Keywords: CARBON NANOTUBES; LONG-LIFE; PERFORMANCE; OXIDE; STORAGE; ELECTRODES; NANOFIBERS; NANOSHEETS; STABILITY; FOAM